Eye Tracking Supported Human Factors Testing Improving Patient Training - Weiss, Kerrin Elisabeth (J Med Syst, 2021)
The handling of left ventricular assist devices (LVADs) can be challenging for patients and requires appropriate training. The devices’ usability impacts patients’ safety and quality of life. In this study, an eye tracking supported human factors testing was performed to reveal problems during use and test the trainings’ effectiveness. In total 32 HeartWare HVAD patients (including 6 pre-VAD patients) and 3 technical experts as control group performed a battery change (BC) and a controller change (CC) as an everyday and emergency scenario on a training device. By tracking the patients’ gaze point, task duration and pump-off time were evaluated. Patients with LVAD support ≥1 year showed significantly shorter BC task duration than patients with LVAD support <1 year (p = 0.008). In contrast their CC task duration (p = 0.002) and pump-off times (median = 12.35 s) were higher than for LVAD support patients <1 year (median = 5.3 s) with p = 0.001. The shorter BC task duration for patients with LVAD support ≥1 year indicate that with time patients establish routines and gain confidence using their device. The opposite effect was found for CC task duration and pump-off times. This implies the need for intermittent re-training of less frequent tasks to increase patients’ safety. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1007/s10916-021-01729-4.